Staff Training and Stress in Long Term Care Facilities Special Care Units for Alzheimer’s Elders - Szilagyi, S. Jean (Magyar Gerontológia, 2021)
Objective: Special Care Units (SCU) in long term care health facilities are named to indicate "unique to diagnosis" or a level of care. The purpose of this study was to explore perceptions among caregivers and licensed nurses in selected nursing homes in Ohio and Pennsylvania and New York, as they pertained to the differences in care to Alzheimer’s elders in SCUs. It examined the education and experience of staff and the satisfaction of this staff as it pertained to stress and wages. Background: Long-term caregivers often experience stress, resulting in "burn-out" as a consequence of limited training, levels of care required, cognitive decline of elders and family expectations. The caregivers, on SCUs, environmentally designed for the elders with cognitive decline, need specialized training in the physical and mental dimensions of the various forms of dementia, Alzheimer’s type. Methods: The study used a qualitative research design with a survey questionnaire and one-on-one interviews with administrators and human resource directors. A pilot study of SCUs in Ohio and Pennsylvania and New York was initiated. The population was the employees of these SCU. The levels of employees questioned included: Executive director/Administrator, nurses, nurse aides, housekeepers and activities staff, laundry and social service workers. The procedure was standardized to enhance the reliability of the data. The respondents were notified in advance of the specific application of their answers and were afforded the opportunity to receive a monetary donation to the SCU of their respective facilities. An Eden Alternative Home, with a program of goals and missions characterizing enhancement of an elder’s life, a home-like environment and family-centered staff and care, in a very rural area of Pennsylvania, was also engaged to contrast and compare the hypotheses of the study. Results: On the SCU, less than 5 percent of the staff had received training specific to the care of the Alzheimer’s elders. In the Eden Home, 100 percent of the staff had received training specific to the care of the Alzheimer’s elders. On the SCU, less than 18 percent were satisfied with the quality and quantity of specialized and extensive training. In the Eden Home, 100 percent of the staff was satisfied with their specific training. On the SCU, using a Leiken scale, more than 55 percent felt that they should receive higher wages. In the Eden home, the results were the same. However, the longevity of the employees was 13.5 years as opposed to only 3.25 years in the SCU in other homes. Conclusion: These findings suggest there is a need to examine, expand and intensify the training of all caregivers on a special unit for the elders afflicted with dementia, Alzheimer’s type.